Phytochemical composition, mineral content and antioxidant activities of the methanol extract of Curcuma longa and Viscum album - Sarah Onyenibe Nwozol; Magdalene Eno Effiong (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2019)
The medicinal value of plants have assumed a more important dimension in the past fewdecades owing largely to the discovery that extracts from plants contain not only minerals and primarymetabolites but also a diverse array of secondary metabolites with antioxidant potentials. However, there isdearth of knowledge on the medicinal uses and nutritional benefits of Curcuma longa and Viscum album. Thisstudy was designed to focus on the phytochemical and mineral composition in addition to the antioxidantactivities of the methanol extracts of C. longa and V. album. Results indicated that the micro and macro mineralanalysis exhibited significant presence of Fe, Zn, Mn, Ca and Mg while Cd, Pb, Ni and Cr were present inminute quantities. Phytochemical screening unravelled the presence of alkaloids, cardiac glycosides, steroids,phenols, tannins, saponins and flavonoids that were also proved by the quantitative analysis. There was a highcorrelation between the flavonoid content and antioxidant activities of the plant extracts. The antioxidantactivities of the extracts were found to be concentration dependent. The results suggest that both plant extractshave good medicinal potentials and can serves as good sources of macro minerals.